The Effectivity of Tomato and Guava Combination Juice and Guava Juice Administration on Blood Glucose Level in Patients with Type II Diabetes Mellitus - ., Hasneli; ., Safyanti; Mardhiyah, Ainil (KnE Life Sciences, 2019)
This study aims to determine the effectivity of tomato and guava juice combination with guava juice on blood glucose levels of patients with type II diabetes mellitus in the work area of Kuranji Padang Health Center in 2019. This quasi-experimental study used a pretest-posttest design with a control group. The population of this study was all patients with type II diabetes mellitus in the working area of Kuranji Health Center, Padang City. Sampling is done by purposive sampling. The number of samples was 24 people, divided into treatment groups and a control group. The data obtained were analyzed by two different dependent tests and an independent t-test. The results of statistical tests showed that there were significant differences between the average decrease in fasting blood glucose levels of respondents who were given tomato and guava combination juice with respondents who were given guava juice (p = 0,026). People with diabetes mellitus are expected to consume tomato and guava combination juice as a form of complementary therapy.